2012
DOI: 10.2460/ajvr.73.2.227
|View full text |Cite
|
Sign up to set email alerts
|

Micro-computed tomography of the head and dentition in cadavers of clinically normal rabbits

Abstract: Micro-CT appeared to be a promising technique for appropriate diagnosis of dental disease in rabbits. Further research is needed to determine the clinical applications of micro-CT imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Computed tomography (CT) overcomes many of the imaging limitations of standard radiography by permitting cross-sectional images of the rabbit head in multiple planes without superimposition of anatomic structures ( 13 , 17 , 18 ). The technique is suitable for early detection of small changes in bone and adjacent soft tissues of the head and provides images of dental anatomy and pathological changes ( 13 , 18 20 ). The use of CT for the diagnosis of dental abnormalities in rabbits is becoming the standard of care ( 13 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Computed tomography (CT) overcomes many of the imaging limitations of standard radiography by permitting cross-sectional images of the rabbit head in multiple planes without superimposition of anatomic structures ( 13 , 17 , 18 ). The technique is suitable for early detection of small changes in bone and adjacent soft tissues of the head and provides images of dental anatomy and pathological changes ( 13 , 18 20 ). The use of CT for the diagnosis of dental abnormalities in rabbits is becoming the standard of care ( 13 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…With conventional CT, the slice thickness and in-slice resolution are usually on the order of 0.5–1.0 mm or higher. When scanning small objects, such as rabbit skulls, visualization of some structures is limited by image spatial resolution ( 18 , 19 ). The disadvantage of the relatively low spatial resolution of CT versus radiographs can be compensated for by the lack of superimposition, ability to view images in multiple planes, and superior contrast resolution ( 18 , 22 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An excellent inter‐ and intraobserver agreement has also been reported in measuring various pituitary gland dimensions on CT images in dogs 8 . Currently, only a few publications detail the normal rabbit head anatomy on CT, 9–11 and only two reports explore the normal rabbit brain on MRI—one on a low‐field (0.2 Telsa) MRI 12 and the other on a high‐field (3 Tesla) MRI 13 . This latter study evaluated the brains of five healthy New Zealand white rabbits on MRI and reported a pituitary gland mean height, width, and length of 3.5, 3.5, and 5.0 mm, respectively 13 .…”
Section: Introductionmentioning
confidence: 99%
“…CBCT has been used in the image-based evaluation of medical conditions in dogs and cats [5], and in anatomical studies on rabbits and guinea pigs [3,6-8]. In most cases, its clinical applications have been limited by low resolution, or an excessively long image processing time [7-9]. …”
Section: Introductionmentioning
confidence: 99%